PERAN PENDIDIKAN KHUSUS DALAM MENINGKATKAN KEMAMPUAN SOSIAL ANAK AUTIS DI SLBN PROF. Dr. SRI SOEDEWI, MS. SH JAMBI - Panji Logowo; Rahmahtrisilvia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the role of special education in improving the social skills of autistic children at SLBN Prof. Dr. Sri Soedewi, MS. SH Jambi. Children with Autism Spectrum Disorder (ASD) face challenges in communication, social interaction, and adaptive behavior, requiring specialized educational approaches. This research employs a qualitative case study method. Data were collected through observation, interviews, and documentation. The findings reveal that individualized learning approaches, visual methods, and collaboration between teachers and parents significantly improve students’ social skills. However, challenges include limited facilities, lack of professional staff, and varied student abilities.